Preacher. Season 1 [videorecording (DVD)]. - Cooper, Dominic, 1978-; Brooke, Tom, 1978-; Brown, W. Earl, 1963- (Sony Pictures Home Entertainment, 2016)
A possessed minister teams up with his ex and a hard-drinking Irish vampire in search of answers.